The prevailing leadership patterns among government secondary school principals in Mafraq Governorate during the Corona pandemic from the point of view of teachers - Alsharafat, Ameera Ayed salem (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the prevailing leadership patterns among government secondary school principals in Mafraq Governorate during the Corona pandemic from the point of view of teachers, and variable effect (Years’ Experience, Education Level) in the views sample. The Study used the analytical method, and the tool consisted of questionnaire Form 26 item divided in to 3 fields it was applied of (186). From teachers. The results also showed no statistically significant differences for variables (sex, years of experience). There are statistically significant differences in the variable level of education in the leadership patterns prevailing among school principals. The result of the study revealed about the general tool got an average of (3.5 out 5) Carriage rating at the Level of Leadership Styles prevalent among government School principals in Mafraq Governorate; the democratic Level obtained the hignest aritnemetic average (3.41 of 5) high degree. Then the chaotic pattern (3. 23) finally the dictatorial pattern (3.10) and both average rate. Based on the results, the researcher submit a number of recommendations to strengthen the democratic pattern and reduce the behavior of the chaotic and dictatorial patterns and the researcher Sub mitted some recommendations: procedure more of the leadership Styles of school principals and their reflection on behavior of teachers. Choosing democratic school leaders and working with teachers in a democratic manner.